Nonlinear Coordinated Passivation Control of Single Machine Infinite Bus Power System with Static Var Compensator - Salma Keskes (IEEE, 2021)
We propose a nonlinear coordinated control of the generator excitation and the static var compensator (SVC) in order to enhance the transient stability and voltage regulation of power system by the passivation approach. SVC is installed in the middle of the transmission line of power system and consists of a single machine infinite bus (SMIB) system. The design of the proposed controller consists of two parts. On one hand, the generator excitation controller is designed based on a backstepping controller. On the other hand, the conception of SVC control input is based on the coordinated passivation approach, which can guarantee the asymptotic stability of the closed-loop system. The simulation results show the effectiveness of the proposed controller compared with other methods, which ensures better performance than the uncoordinated control when the system is subjected to a disturbance.